Effects of Red Light Illumination on Productivity, Fertility, Hatchability and Energy Efﬁciency of Thai Indigenous Hens - Gongruttananun, Nirat; Guntapa, Pannapat (Agriculture and Natural Resources, 2012)
This study was conducted to determine the effects of red light exposure on the productivity, fertility and hatching characteristics in Thai native hens (Gallus domesticus). A total of 120 birds aged 18 wk were housed in an open-sided shed and exposed to one of the following lighting treatments: 1) natural daylight supplemented with ﬂ uorescent light (Control), 2) natural daylight supplemented with red light (NR) and 3) red light as the sole light source (R). The red light was produced by light- emitting diodes. All treatments were provided with a daily light:dark photoperiod of 16:8 hr over a 28-week egg-laying period, and there were four replicate pens of 10 hens for each treatment. Photostimulation of the light sources was initiated at age 18 wk and any subsequent effects on the live performance and reproductive traits were observed during the experimental period. Feed and water were available at all times. Body weights, feed consumption and mortality rates were similar among the treatment groups. The age at ﬁ rst egg of the NR birds (130.7 d) was comparable to that of the R birds (129.2 d) which was signiﬁ cantly less than that of the control hens (134.7 d). During the ﬁ rst week of the laying period, R hens produced more eggs than did hens in the control treatment (P < 0.05), whereas the NR birds exhibited an intermediate value between those groups. At 2 wk after photostimulation, the serum estradiol concentration was signiﬁ cantly higher for hens in the R treatment compared to those of the control and NR treatments. The hematocrit values of the birds in the R treatment tended to be lower than those of the other two treatments in some periods of the study. During the lighting period from weeks 6 to 8, a signiﬁ cantly improved feed conversion ratio was observed in the R and NR treatments compared to that of the control treatment. No signiﬁ cant differences in egg weight, egg and eggshell quality or any parameters of hatching occurred between the R and control groups. The weights of the ovary, pituitary gland, spleen and the abdominal fat were similar for all light treatments. It was concluded that photostimulation by red light resulted in an acceleration of sexual development in Thai native hens compared to hens exposed to full-spectrum lighting; however, live performance, egg production, egg and eggshell quality, and fertility were not affected whatever the light treatment. The light-emitting diode lighting regimens could be beneﬁ cial for energy conservation and the reduction of rearing costs in laying hens.